Effects of processing on onion skin powder added extrudates - Tonyali, Bade (J Food Sci Technol, 2020)
It is possible to enhance the functional properties of extruded products with the inclusion of fruit and vegetable by-products. Onion skin, a rich source of quercetin and fiber, is considered as waste in the industry and can be used as an alternative ingredient to improve the nutritional value of the extruded products. Three levels (3, 6, and 9%) of onion skin powder (OSP) were added to wheat flour and compared with control (0% OSP). The effect of the extrusion process on accessible quercetin, total phenolic content, and antioxidant activity of the samples were investigated. In addition, carbohydrate digestibility analyses were conducted for the products. Mass spectrometry (LC–MS/MS) results indicated that increasing the OSP level increased the quercetin content. The process caused the release of the entrapped quercetin from OSP, which was revealed by significantly higher quercetin levels for the extrudates. Some of the quercetin was lost during in vitro digestion process. Increasing the OSP level increased antioxidant activity and total phenolic contents of the samples. Total phenolic contents decreased significantly after the processing, yet antioxidant activities were not affected. The extruded products showed high amounts of rapidly available glucose (69.5 g/100 g). The OSP enhancement did not change the carbohydrate digestibility of products. The results indicated that the extrusion process could increase the level of accessible bioactive ingredients, and the level of functional compound addition can be optimized further.